2023
DOI: 10.3390/ph16040512
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease

Abstract: Background: Steroid-refractory acute graft-vs.-host disease (SR-aGVHD) is a complication of allogeneic hematopoietic stem cell transplantation with a dismal prognosis and for which there is no consensus-based second-line therapy. Ruxolitinib is not easily accessible in many countries. A possible therapy is the administration of mesenchymal stromal cells (MSCs). Methods: In this retrospective study, 52 patients with severe SR-aGVHD were treated with MSCs from umbilical cord (UC-MSCs) in nine institutions. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Non-invasive access, higher proliferative capacity, lower immunogenicity, and the absence of ethical issues make them an ideal source for stem cell transplantation therapy [ 1 , 2 ]. Many preclinical studies and clinical trials have been carried out with good success in HucMSCs for the treatment of a wide range of pediatric diseases [ 3 , 4 ]. Interestingly, one study showed that MSCs were more effective in pediatric patients than in adult patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive access, higher proliferative capacity, lower immunogenicity, and the absence of ethical issues make them an ideal source for stem cell transplantation therapy [ 1 , 2 ]. Many preclinical studies and clinical trials have been carried out with good success in HucMSCs for the treatment of a wide range of pediatric diseases [ 3 , 4 ]. Interestingly, one study showed that MSCs were more effective in pediatric patients than in adult patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive access, higher proliferative capacity, lower immunogenicity, and the absence of ethical issues make them an ideal source for stem cell transplantation therapy 1,2 . Many preclinical studies and clinical trials have been carried out with good success in HucMSCs for the treatment of a wide range of pediatric diseases 3,4 . Interestingly, one study showed that MSCs were more effective in pediatric patients than in adult patients 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow transplant units are now rapidly expanding into the cellular therapy arena as car-T, NK cells, adoptive anti-virus specific T cells, and mesenchymal cells for GVHD are increasingly being used ( 30 32 ).…”
mentioning
confidence: 99%